Improving nurses’ ESP communicative competence by digital storytelling method - Anita Purba; Semaria Eva Elita Girsang; Tiodora Fransiska Silalahi; Erikson Saragih (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
The quality of Indonesian nurses promoted to work abroad is greatly affected by their ability to communicate in medical English. A number of previous studies have explored the effectiveness of using digital storytelling in the foreign language learning process. However, research on the application of this method to improve communication competence in ESP nursing is still very limited. This research aims to test the effectiveness of using the Digital Storytelling (DST) method on nurses’ English communication competence. Using classroom action research design, with 125 nurses’ samples, the study proves that there is a significant effect on nurses' communication skills (grammatical competence, strategic competence, and sociolinguistic competence). In addition, the majority of the students responded positively to the use of this method, particularly in terms of increasing their confidence in communicating in English in general and medical English in particular. The strength and limitations of this method are also discussed in this study.